Hydroamnion Associated with Fetal Deformity and Prolonged Gestation in a Crossbreed Jersey Cow - Shanawaz, Shaik Mohammad; Charan, Patruni Sri; Anusha, Konjeti; Kalyani , Bachu (The Indian Journal of Animal Reproduction, 2025)
A primiparous crossbreed Jersey cow with history of prolonged gestation and abdominal distension was presented.  Parturition was induced with cloprostenol sodium and dexamethasone. After 48hrs the cervix was fully dilated and the  water bag was ruptured with a bp blade approximately 40-50 liters of fluid gushed out. Based on the appearance of fluid  the case was diagnosed as Hidramnion. Partial fetotomy was done and then a stab incision on ventral abdomen of fetus  to remove accumulated fluid. Forced traction was applied to deliver deformed fetus.
Keywords: Prolonged Gestation; Hidramnion; Partial Fetotomy; Fetal Deformity